Cowgirl Kate and Cocoa - Silverman, Erica; Lewin, Betsy (Orlando Harcourt, 2005)
Cowgirl Kate and her cowhorse Cocoa, who is always hungry, count cows, share a story, and help each other fall asleep.
Keywords: Cowgirls -- Fiction; Horses -- Fiction